The Practice of Paddy Field Pawn and Its Impact on the Welfare of Al-Rahin Viewed from an Islamic Perspective - Ulpaziah; H. Busaini; M. Huzaini (Tinta Emas Institute, 2023)
This research aims to find out how the practice of pawning rice fields carried out by the farming community in Jerowaru Subdistrict, the impact of the rice field pawn system on the welfare level of Al-Rahin, and evaluate whether the practice of pawning rice fields is in accordance with the Islamic perspective. This research uses a qualitative method with a descriptive approach. Respondents in this study were 10 people. Data collection techniques were carried out by field observation, interviews and documentation. The results of this study indicate that the practice of pawning rice fields carried out in Jerowaru District begins with the rahin coming to the murtahin to borrow money with a rice field pawn agreement. Judging from an Islamic perspective, the practice carried out by Al-Rahin in Jerowaru Subdistrict is not yet appropriate. In terms of the pillars and conditions of the pawn have been fulfilled, but in its implementation it was found that the murtahin utilized the pledged rice field until the rahin was able to pay it off because there was no time limit specified. In addition, the right to manage the rice fields fully falls into the hands of the murtahin. In the practice of pawning rice fields, Al-rahin gets welfare in terms of material elements, namely the fulfillment of clothing, food and shelter. However, Al-rahin does not get welfare from the spiritual element, namely peace, spaciousness, and peace of mind.